2010
DOI: 10.1080/03079457.2010.527923
|View full text |Cite
|
Sign up to set email alerts
|

Ascarid infections in laying hens kept in different housing systems

Abstract: The present study was undertaken to investigate the prevalence of ascarid infections in Swedish commercial laying hens in 2004 and 2008 following a recent nationwide change to alternative housing systems but before anthelmintics became available. Also, the influence on prevalence of farm and flock characteristics and management was studied in 2004. The results showed that the overall prevalence was significantly higher in 2008 (38%; n 0 64/169) compared with 2004 (24%; n 0 44/186) (P 0 0.001). Ascarid infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 17 publications
4
46
0
Order By: Relevance
“…All six flocks studied were introduced into the barns as replacement pullets at age 14-16 weeks between May and August 2009. Housing and feeding of commercial laying hens in Sweden has been previously described (Jansson et al, 2010).…”
Section: Study Farmsmentioning
confidence: 99%
See 2 more Smart Citations
“…All six flocks studied were introduced into the barns as replacement pullets at age 14-16 weeks between May and August 2009. Housing and feeding of commercial laying hens in Sweden has been previously described (Jansson et al, 2010).…”
Section: Study Farmsmentioning
confidence: 99%
“…The first faecal sample for parasitology was taken about a week after the birds arrived at the farm, to verify the hens' initial infection status. On each sampling occasion four samples of 100 g pooled fresh faeces were collected as previously described (Jansson et al, 2010). Samples were obtained in the same way throughout the study on each farm and were sent overnight by surface mail to the National Veterinary Institute (SVA), Uppsala, Sweden, for detection and identification of parasite eggs using a modified McMaster method based on saturated salt as flotation medium but with a detection level of 20 eggs per gram (epg) faeces (Permin and Hansen, 1998).…”
Section: Sampling and Parasitological Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-caged hens, this change was accompanied by a rapid increase of roundworm infections, especially Ascaridia galli [13]. The source of these nematodes and routes of transmission between farms have not been clearly identified, but previous studies have suggested indirect transmission between farms rather than introduction via infected replacement pullets [13,14]. To explore this further, more detailed studies based on the genetic relationships between worms collected from different flocks are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Stocking rate, removal of manure, biosecurity measures, disinfection procedures and production according to the "all in-all out" principle have apparently decreased the significance of parasitic infection (Permin et al 1998;Jansson et al 2010). Although management may control transmission of parasites with intermediate hosts in commercial free-range system (Permin et al 1999), at this time there is no effective way to prevent and eliminate the existing parasitic infections in non-cage production systems.…”
Section: Statement Of Problemmentioning
confidence: 99%